2002
DOI: 10.2355/isijinternational.42.551
|View full text |Cite
|
Sign up to set email alerts
|

Bauschinger Effect in .ALPHA.-.GAMMA. Dual Phase Alloys Studied by In Situ Neutron Diffraction.

Abstract: In situ neutron diffraction experiments during tension-compression deformation were performed on five Fe-Cr-Ni alloys with the volume fraction of ferrite (a) ranging from 0.0 to 100 %. Tensile deformation was applied in a step by step manner up to a strain of 1.3-2.0 % followed by compressive deformation, and neutron diffraction spectra were recorded during temporary stops of a deformation machine with fixed crosshead. (111) reflection of austenite and (110) of ferrite, respectively, were measured simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…linearity at a strain of 0.06, while ε 110 B2 continues to rise linearly. This indicates the onset of yielding in g, at the microscopic level, due to its lower yield stress than that of B2 [39]. Exactly from this very moment, the stress shifts from g to the still elastic B2.…”
Section: Strain Partitioning From Aspect Ratio Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…linearity at a strain of 0.06, while ε 110 B2 continues to rise linearly. This indicates the onset of yielding in g, at the microscopic level, due to its lower yield stress than that of B2 [39]. Exactly from this very moment, the stress shifts from g to the still elastic B2.…”
Section: Strain Partitioning From Aspect Ratio Measurementsmentioning
confidence: 99%
“…This stage is marked as II 1 in Fig. 6c, reflecting the "grain to grain yielding" in g due to the varying Schmid factor and strain hardening of individual grains [39,57]. As the strain increases to 0.07, a rapid drop of ε 110 B2 appears, which signals the onset of the stage II 2 .…”
Section: Strain Partitioning From Aspect Ratio Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22) In a TRIP assisted multi-structure steel for automobile use, carbon enriched austenite is found to be harder than ferrite.…”
Section: Improvement Of Ductility By Using the Second Phasementioning
confidence: 99%
“…The back-stress-induced strain hardening has been reported to contribute to the large uniform elongation in TWIP steels, 1,14 TRIP steels, 15 and DP steels. 16,17 In our previous research, 18 we have also shown that the HSSS developed by Kim et al 13 is better understood as a dual-phase microstructure since the B2 phase is deformable. Moreover, the stress/strain partitioning and the back-stress-induced strain hardening have been proven to play an important role during the plastic deformation for this HSSS based on in situ high energy X-ray diffraction data, scanning electron microscopy (SEM) images of samples before and after tensile tests, and the back stress measurement from tensile load-unloadreload (LUR) tests.…”
Section: Introductionmentioning
confidence: 99%